'Miscarriage or abortion?' Understanding the medical language of pregnancy loss in Britain; a historical perspective. Issue 2 (21st February 2013) - Moscrop, Andrew
Abstract : Clinical language applied to early pregnancy loss changed in late twentieth century Britain when doctors consciously began using the term 'miscarriage' instead of 'abortion' to refer to this subject. Medical professionals at the time and since have claimed this change as an intuitive empathic response to women's experiences. However, a reading of medical journals and textbooks from the era reveals how the change in clinical language reflected legal, technological, professional and social developments. The shift in language is better understood in the context of these historical developments, rather than as the consequence of more empathic medical care for women who experience miscarriage.